2019
DOI: 10.1139/apnm-2018-0281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of video game playing and a glucose preload on subjective appetite, subjective emotions, and food intake in overweight and obese boys

Abstract: Video game playing (VGP) is associated with overweight/obesity (OW/OB). VGP and caloric preloads in the pre-meal environment influence short-term food intake (FI) in healthy weight children. Therefore, the purpose of the present study was to examine the effect of pre-meal VGP and a glucose preload on subjective emotions, subjective appetite, and FI in boys with OW/OB. On four separate mornings, boys with OW/OB (n = 22; mean±SD: age = 11.9±1.6 years; BMI percentile = 94.3±3.9) participated in four test conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Symptoms may persist for a short period (10 min) or a relatively long one (even 4 h) 3 Fernández et al ( 2018 ) Research article * Modelling of a cell phone held to the ear, or VR devices in front of the eyes reveal that young eyes and brains absorb substantially higher local radiation doses than adults. Age-specific simulations indicate the need to apply refined testing methods and for public education regarding manufacturers' advice to keep phones off the body, and prudent use to limit exposures, particularly to protect the young 4 Fuller et al ( 2017 ) Research article * * Using any device at bedtime was associated with a statically significant increased use of multiple forms of technology at bedtime and use in the middle of the night, reducing sleep quantity and quality and elevating body mass index 5 Gheller et al ( 2019 ) Research article * Video game playing (VGP) is associated with overweight/obesity (OW/OB). VGP and caloric preloads in the pre-meal environment influence short-term food intake (FI) in healthy-weight children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms may persist for a short period (10 min) or a relatively long one (even 4 h) 3 Fernández et al ( 2018 ) Research article * Modelling of a cell phone held to the ear, or VR devices in front of the eyes reveal that young eyes and brains absorb substantially higher local radiation doses than adults. Age-specific simulations indicate the need to apply refined testing methods and for public education regarding manufacturers' advice to keep phones off the body, and prudent use to limit exposures, particularly to protect the young 4 Fuller et al ( 2017 ) Research article * * Using any device at bedtime was associated with a statically significant increased use of multiple forms of technology at bedtime and use in the middle of the night, reducing sleep quantity and quality and elevating body mass index 5 Gheller et al ( 2019 ) Research article * Video game playing (VGP) is associated with overweight/obesity (OW/OB). VGP and caloric preloads in the pre-meal environment influence short-term food intake (FI) in healthy-weight children.…”
Section: Resultsmentioning
confidence: 99%
“…There is often a vicious cycle as, when children are engaged in an interesting game with great immersion, there is a risk of obesity, due to unhealthy eating habits and lack of physical activity. Obesity can lead to sleep disorders, but also sleep disorders due to blue light and low melatonin levels can lead to obesity with possible cardio-metabolic deficiencies factors (Calvert et al 2013 ; Tosini et al 2016 ; Turel et al 2016 , 2017 ; Fuller et al 2017 ; Kenney and Gortmaker 2017 ; Cappuccio and Miller 2017 ; Gheller et al 2019 ). Limiting screen time in children and adolescents from one to two hours before bedtime and, at the same time, using protective equipment, such as glasses that block blue light, can prevent sleep disorders and consequently their associated problems (Gottschalk 2019 ; Boyd 2020 ).…”
Section: Summary and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments 1 and 2, participants were asked to complete visual analogue scales (VAS) for motivation-to-eat and physical comfort; each VAS was a 100 mm line where they placed a pencil mark to describe their feelings along the continuum. For motivation-to-eat, children described their desire to eat (“Very weak” to “Very strong”), hunger (“Not hungry at all” to “As hungry as I have ever felt”), fullness (“Not full at all” to “Very full”), and prospective food consumption (PFC) (“A large amount” to “Nothing at all”) for subjective appetite, as reported [ 34 , 35 , 36 , 37 ] and validated [ 27 ] in our previous studies. A subjective appetite score was calculated from the motivation-to-eat VAS questionnaire using the following formula: Subjective Appetite (mm) = [desire to eat + hunger + (100 − fullness) + PFC]/4.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in their meta-analytic reviews, Moher et al (2009) found that low self-control often results in increased consumption of alcohol and tobacco as well as uncontrolled eating. Gheller et al (2019) examined the causal influences of video game playing (VGP) on emotions, appetite, and food intake. They found that negative emotions evoked after VGP positively influenced food intake and subjective appetite; on the other hand, participants who felt positive emotions after VGP desired to eat less, demonstrating high self-control and the ability to resist palatable foods.…”
Section: Methodsmentioning
confidence: 99%